Development of a Diagnostic Clinical Score for Hemodynamically Significant Patent Ductus Arteriosus - Kindler, Annemarie; Seipolt, Barbara; Heilmann, Antje; Range, Ursula; Rüdiger, Mario; Hofmann, Sigrun Ruth (Frontiers in Pediatrics, 2017)
There is no consensus about the hemodynamic significance and therefore the need to treat a persistent ductus arteriosus in preterm newborns. Since the diagnosis of a hemodynamically-significant persistent ductus arteriosus (hsPDA) is made by a summary of non-uniform echo-criteria in combination with the clinical deterioration of the preterm neonate, standardized clinical and ultrasound scoring systems are needed. The objective of this study was the development of a clinical score for the detection and follow-up of hsPDA .compared to echocardiography, which should help to confirm hemodynamic significance. In this observational cohort study of 154 preterm neonates (mean gestational age 28.1 weeks), clinical signs for the development of hsPDA were recorded in a standardized score and compared to echocardiography. Analyzing the significance of single score parameters compared to the diagnosis by echocardiography, we developed a short clinical score (calculated sensitivity 84% and specificity 80%). In conclusion, this clinical diagnostic PDA-score is non-invasive and quickly to implement. The continuous assessment of defined clinical parameters allows for a more precise diagnosis of hemodynamic significance of PDA and therefore should help to detect preterm neonates needing PDA-treatment. The score therefore allows a more targeted use of echocardiography in these very fragile preterm neonates.